Perception of Smile Aesthetics between Orthodontists and Moroccan Patients - Abdoul Haizou Rabe; Yosra Tabchi; Fatima Zaoui; Azaroual Mohamed Faouzi; Asmae Bahoum (Indian Journal of Dental Research)
Introduction: One of the main goals of orthodontic management is to achieve a beautiful smile. However, beauty has both objective and subjective dimensions. This study aims to evaluate the factors that affect the perception of the smile in patients consulting for orthodontic treatment about the vision of their practitioners. Materials and Methods: Fifty orthodontic patients and 30 orthodontists evaluated the degree of attractiveness of 16 photographs of the smile. Dental, gingival and labial parameters were used. Statistical analyses of the level of perception of each group were performed. The Student t-test and the Chi-square test were used to compare the attractive and unattractive smile parameters. Results and Discussion: The perception of smile aesthetics between orthodontists and orthodontic patients has shown a significant difference (P < 0.05). Orthodontists were more analytical in judging variables like smile arc, alterations of the gingival display and the palatal inclination of the maxillary incisors.